Student Worksheet Based on Realistic Mathematics Education Approach on Multiplication and Division Material for Grade V Elementary School - Monika, Dinda; Ramadan, Zaka Hadikusuma (Universitas Pendidikan Ganesha, 2022)
Teachers have not provided Student Worksheets based on the Realistic Mathematical Education (RME) approach. This has an impact on the low understanding of fifth-grade students. This study aims to develop worksheets based on the realistic mathematic education (RME) approach and analyze the development of worksheet validity based on practical mathematic education (RME) approach on multiplication and fraction division material for fifth-grade elementary school students. This type of research is development research using the ADDIE procedure. The methods used in data collection are interviews, documentation, and questionnaires. The data collection instrument is in the form of a questionnaire. Data analysis techniques are qualitative descriptive analysis and quantitative descriptive analysis methods. The results showed that the worksheet based on a realistic mathematical education (RME) approach was valid from the material, media, learning design, and language experts. This study concludes that the learning media in the form of a worksheet based on a realistic mathematical education (RME) approach is feasible and effective in the mathematics learning process, especially in equations and fraction division.